Role of microRNAs in myeloid differentiation. (19th November 2008) - Fatica, Alessandro; Rosa, Alessandro; Ballarino, Monica; Marchis, Maria Laura De; Rasmussen, Kasper D.; Bozzoni, Irene
Abstract : All types of blood cell of the body are continuously produced by rare pluripotent self-renewing HSCs (haemopoietic stem cells) by a process known as haemopoiesis. This process provides a valuable model for examining how genetic programmes involved in cell differentiation are established, and also how cell-fate specification is altered in leukaemia. Here, we describe examples of how miRNAs (microRNAs) can influence myelopoiesis and how the identification of their target mRNAs has contributed to the understanding of the molecular networks involved in the alternative control between cell growth and differentiation. Ectopic expression and knockdown of specific miRNAs have provided powerful molecular tools able to control the switch between proliferation and differentiation, therefore providing new therapeutic tools for interfering with tumorigenesis.